The Effect of Gemini AI Accuracy Perception and Digital Literacy on Students' Economic Learning Outcomes - Devi Avrilia; Wida Wulandari (Universitas Negeri Medan, 2026)
The use of artificial intelligence (AI) in education continues to increase along with the development of digital technology and ease of access to information. Gemini AI can help students understand the material and complete tasks more effectively, but it also has the potential to generate dependency if not balanced with adequate evaluation skills. This study aims to analyze the effect of Gemini AI Accuracy Perception and digital literacy on economic learning outcomes of students in SMA Negeri 4 Sidoarjo. This study uses a quantitative approach with SEM-PLS analysis technique using WarpPLS software. The sample consisted of 158 students selected through simple random sampling. Data collection is done through questionnaires. The results showed that the perception of accuracy Gemini AI and digital literacy have a positive and significant effect on students economic learning outcomes, with coefficient values of 0.301 and 0.347, respectively. The R2 value of 0.311 indicates that there are 68.9% of other factors that influence learning outcomes, such as teaching methods, motivation, and learning environment. Thus, the 31.1% contribution of both variables remained meaningful as predictors of learning outcomes, particularly in the context of behavioral and educational research that emphasizes the identification of key predictors.